2022
DOI: 10.1513/annalsats.202006-722oc
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Exacerbation Risk by Body Mass Index in Patients with COPD in TIOSPIR and UPLIFT

Abstract: Rationale There is an association between body mass index (BMI) and mortality in chronic obstructive pulmonary disease (COPD), with underweight individuals having higher mortality risk. Mortality and exacerbation risks among individuals with higher BMI are unclear. Objectives To examine the relationship between BMI and adverse outcomes in COPD. Methods This post hoc analysis included data from TIOSPIR (Tiotropium Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Therefore, it is necessary to explore the relationship between exacerbation, mortality, symptoms improved or deteriorated and clinical characteristics including BMI in COPD patients. In fact, several studies have been demonstrated that the patients with low BMI had a higher future risk of exacerbation and mortality [2][3][4][5][6]8]. In this study, we also found that low BMI patients had a higher future risk of hospitalizations and mortality during one year of follow up.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Therefore, it is necessary to explore the relationship between exacerbation, mortality, symptoms improved or deteriorated and clinical characteristics including BMI in COPD patients. In fact, several studies have been demonstrated that the patients with low BMI had a higher future risk of exacerbation and mortality [2][3][4][5][6]8]. In this study, we also found that low BMI patients had a higher future risk of hospitalizations and mortality during one year of follow up.…”
Section: Discussionsupporting
confidence: 72%
“…This might be associate with the social economic conditions in the previous year in China. In addition, Putcha et al [3] found that baseline FEV1%pred and FEV1/FVC were lower in low BMI groups. In our study, we also found that the low BMI had a worse pulmonary function.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, our research results show that more symptomatic patients had a lower BMI but a higher risk of future exacerbation and mortality. This was consistent with a study by Putcha et al , 35 which showed that underweight participants had a significantly higher risk of death and severe exacerbation.…”
Section: Discussionsupporting
confidence: 93%